Gramática como habilidade no ensino-aprendizagem de língua inglesa: um estudo sobre implicações na acuidade da produção lingüística e percepções dos aprendizes a essa proposta - Linhares, Maria José Xavier (2010)
Research on grammar involving teaching-learning English as a foreign language has shown the necessity to change the focus on the way grammar has been taught in communicative classrooms. Much inquiring has been elicited concerning the best way to teach grammar so that it can contribute to the learners accuracy. The aim of this investigation is to analyze the process and the results, as studying a group of university students at a public university in Sao Paulo State, related to oral and written accuracy. We based our discussions and pedagogical activities design mainly on Batstone (1994) and Larsen-Freeman proposals (2003), called, respectively, Grammar as Skill and Grammaring. Besides being based on themes, the course design has followed two elements of the grammar as skill: noticing and reflection, which have guided the activities and the development of the classes as well as their perception to this grammar approach. Students proved to be receptive to this type of teaching grammar inductively, being able to use it in their oral and written linguistics production.